The Effect of the Peer Teaching Model on Students’ Underhand Passing Skills in Volleyball at SMA Santa Maria 3 Cimahi - Angelina Chyntia; Aep Rohendi; Ani Pristiawati (Journal of Physical and Outdoor Education, 2026)
In physical education learning at schools, various instructional models are available, one of which is peer teaching. This model can be utilized as an assistive method in the teaching and learning process, particularly in physical education. The lack of effectiveness in physical education learning is often caused by the teacher’s inability to apply diverse teaching strategies, resulting in monotonous lessons and reduced student enthusiasm. The purpose of this study is to determine the effect of the peer teaching model on students' learning outcomes in underhand passing in volleyball at SMA Santa Maria 3 Cimahi. This research employed an experimental method with a population consisting of two 10th-grade classes and a sample of 65 students. The independent variable in this study is the peer teaching learning model (X), and the dependent variable is the underhand passing skill (Y). The t-test results showed a significance value (2-tailed) of 0.000 < 0.05, indicating that H₀ is rejected and H₁ is accepted. This means there is a significant effect of the peer teaching model on the learning outcomes of underhand passing.